Hospitalists caring for patients with advanced cancer: An experience‐based guide. Issue 4 (20th November 2015) - Koo, Douglas J.; Tonorezos, Emily S.; Kumar, Chhavi B.; Goring, Tabitha N.; Salvit, Cori; Egan, Barbara C.
Abstract : Every year, nearly 5 million adults with cancer are hospitalized. Limited evidence suggests that hospitalization of the cancer patient is associated with adverse morbidity and mortality. Hospitalization of the patient with advanced cancer allows for an intense examination of health status in the face of terminal illness and an opportunity for defining goals of care. This experience‐based guide reports what is currently known about the topic and outlines a systematic approach to maximizing opportunities, improving quality, and enhancing the well‐being of the hospitalized patient with advanced cancer. Journal of Hospital Medicine 2016;11:292–296. © 2015 Society of Hospital Medicine